The Evolution of Classical Spiro-OMeTAD: Synthesis of Arylamine Endcapped Indenone Spirofluorene - Liu, Shihui; Yi, Xiaoqing; Wang, Hao; Ye, Tao; Wang, Kui; Cao, Wei; Guan, Jing; Fan, Ruiqing; Yang, Yulin; Hao, Sue; Xia, Debin (Frontiers in Chemistry, 2022)
Spiro-OMeTAD is the well know hole transporting material (HTM) in perovskite solar cells. In this work, its derivatives, namely four D-A shaped triphenylamine or biphenylamine endcapped indenone spirofluorene (SFD-TPA, SFD-OMeTPA, SFD-TAD and SFD-OMeTAD) were designed and synthesized. With introduction of electron withdrawing moieties and the extension of conjugation length, a serious of changes in photophysical and electrochemical properties could be detected. Notably, in comparison with the optical gap (2.96 eV) of the reported Spiro-OMeTAD, SFD-OMeTAD presents the optical gap as low as 1.87 eV. Moreover, density functional theory simulations were employed to further investigate their geometric and electronic structures. Finally, steady-state photoluminescence measurements proved the efficient charge separation and collection processes at the perovskite/HTM interface. It can be predicted that all the four compounds with enhanced sunlight absorption capability and suitable frontier energy levels, can be used as hole transporting materials for perovskite solar cells.